mos gene transforming efficiencies correlate with oocyte maturation and cytostatic factor activities. - Yew, N (1991)
The mos proto-oncogenes from different vertebrate species transform mouse NIH 3T3 cells with markedly different efficiencies. v-mos, mouse (c-mosmu), and chicken (c-mosch) mos transform NIH 3T3 cells 10- to 100-fold more efficiently than do human (c-moshu) and Xenopus (c-mosxc) mos. The mos genes with the highest transforming activity efficiently induce maturation in Xenopus oocytes and mimic cytostatic factor (CSF) by causing mitotic cleavage arrest in embryos. Chimeric v-mos/c-moshu proteins that had high transforming efficiencies in NIH 3T3 cells were also effective in the induction of oocyte maturation and CSF cleavage arrest. We measured the in vitro autophosphorylation activities of the different mos proteins and found that the levels of kinase activity of v-mos, c-mosmu, and c-mosch were much higher than that of c-mosxc. These data indicate that mos gene transforming efficiency and the ability to induce oocyte maturation or mimic CSF activity are correlated with in vitro autophosphorylation activity and suggest that the mos protein plays a similar role in transformed cells and normal oocytes.